Environmental Services Provided by Tampa's Urban Forest - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
FOR-204, a 5-page illustrated fact sheet by Michael G. Andreu, Melissa H. Friedman, and Rob J. Northrop, provides a brief overview and results from an urban ecological assessment conducted in the city of Tampa from February to July 2007. Includes references. Published by the UF School of Forest Resources and Conservation, January 2009.